Why Bureaucratic Stability Matters for the Implementation of Democratic Governance Programs. Issue 2 (22nd April 2013) - Cornell, Agnes
<x xml:space="preserve">Abstract</x> The theoretical framework developed in this article suggests that high turnover rates in the public administrations of aid‐recipient countries present a challenge to the implementation of democratic governance (DG) aid. If high turnover rates are due to individuals' search for better opportunities, it will affect the implementation primarily through lack of experience and shorter time horizons among civil servants. However, if high turnover rates are due to political appointment of personnel, there is an additional negative factor that will affect the implementation: the reluctance to engage in old projects. Hence, high turnover rates affect the implementation of DG programs negatively, especially if caused by political appointment. These mechanisms are shown to be at work in interviews with donors and recipients of a broad range of DG programs in Peru and Bolivia.